Effect of Genetic Parameters on Some Growth Performance Traits of Harnai Sheep - Abdul Sattar Safi; Hubdar Ali Kaleri; Gul Muhammad; Rameez Raja Kaleri; Asma Kaleri; Muhammad Akram Safi; Assad Ullah; Kamal Uddin Mandokhial; Muhammad Siddiq (Journal of Basic & Applied Sciences, 2017)
Present study was performed to estimates the genetic parameters forsome growth performance traits of Harnai sheep. The data was recorded for the period of 2004-2013 from the Multi-purpose research centre Yetabad, District, Baluchistan. The performance traits including birth, yearling, weaning and fleece weight was recorded for the estimation of genetic parameters. There was no significant difference was observed parity and Ram wise among some growth performance traits of Harnai sheep. While the results for heritability, estimation for birth weight, yearling weight, weaning weight and fleece weight was observed low to medium for some growth performance traits of Harnai sheep. It is concluded that low heritable and correlative traits mainly affected by the management, nutritional and temporary environmental conditions, hence improvement can be achieved through the better selection.